2020
DOI: 10.1093/jee/toaa195
|View full text |Cite
|
Sign up to set email alerts
|

Sap Beetles (Coleoptera: Nitidulidae) in Oak Forests of Two Northeastern States: A Comparison of Trapping Methods and Monitoring for Phoretic Fungi

Abstract: Oak wilt is slowly expanding in the northeastern United States. Several nitidulid beetle species are known vectors of the fungus [Bretziella fagacearum (Bretz) Z. W. De Beer, Marinc., T. A. Duong, and M. J. Wingf (Microascales: Ceratocystidaceae)] that causes this disease, acquiring spores from fungal mats on infected trees and transmitting them to uninfected trees. Survey and fungal isolation from captured nitidulid beetles could be an important tool for detecting the presence of this disease in a geographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The beetles collected in wet collection traps were not used for culturing due to the sterilizing ability of the propylene glycol commonly used in wet trapping systems. The results showed that multiple‐funnel trap with wet collection cups caught higher abundances and more diverse groups of nitidulids in New York (DiGirolomo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The beetles collected in wet collection traps were not used for culturing due to the sterilizing ability of the propylene glycol commonly used in wet trapping systems. The results showed that multiple‐funnel trap with wet collection cups caught higher abundances and more diverse groups of nitidulids in New York (DiGirolomo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…New York began trapping nitidulid beetles in 2017 as part of a multi‐state effort to determine (1) which trap types collected the highest abundance and diversity of nitidulid beetles and (2) to determine if oak wilt could be cultured from beetles collected in wind‐oriented dry collection traps (DiGirolomo et al, 2020). Oak wilt was not successfully cultured from dry‐collected beetles during the study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flying beetles were collected using four types of traps; wind-oriented funnel traps, 12-unit Lindgren funnel traps, 12-unit modified Lindgren funnel traps, and 5-unit Synergy multitraps (Synergy Semiochemical Corp. Delta, BC ). Wind-oriented funnel traps are also referred to as PVC pipe traps and wind-oriented pipe traps ( Dowd et al 1992 ; DiGirolomo et al 2020 ). Three traps were placed at least 10 m apart at 16 localities in Ontario and Manitoba.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Oak trees are susceptible to this fungus with some species dying within weeks of the initial infection. Oak wilt can infect neighboring trees through root-to-root contact ( Bruhn et al 1991 ), however transmission by nitidulids is considered more concerning because of the potential for transmission over greater distances and the formation of many new infection epicenters ( DiGirolomo et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%